Formative Modernities in the Early Modern Atlantic and Beyond
XXXIII, 359 p. 16 illus.
Keywords: This book offers a new perspective on the concept of modernity. Since its invention as a contrast to Antiquity or the Middle Ages, modernity has been tied to ideas of superiority, progress, and efficiency. As a counterpart to the Marxist “history of class struggle”, “modernization theories” have transformed modernity into an almost teleological concept of historical development. These strong connotations obstruct a clear look at other forms of modernity. The contributions of the volume will show in a comparative perspective how modernity can also be understood and analyzed as multiple responses of societies and polities to organize themselves in facing ever more complex and integrated interactions at ever larger scales.